Testing the Sticky Information Phillips Curve - Coibion, Olivier (The Review of Economics and Statistics, 2010)
I consider the empirical evidence for the sticky information model relative to the basic sticky price model, conditional on historical measures of inflation forecasts. The estimated structural parameters are inconsistent with an underlying sticky information model and the sticky information Phillips curve is statistically dominated by the new Keynesian Phillips curve. I find that the poor performance of the sticky information approach is driven by two key elements. First, the sticky information model underestimates inflation in the 1970s and overestimates inflation since the 1980s. Second, predicted inflation from the sticky information model is excessively smooth.